Koder, kapital og kurerer. Nye vinkler på Kominterns hemmelige apparat - Møller, Morten; Rosenfeldt, Niels Erik (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
Morten Møller & Niels Erik Rosenfeldt: Codes, capital and couriers – new angles on the Comintern’s secret apparatus The article presents and analyses for the first time in a Danish context central parts of Comintern’s secret communications by radio between the headquarters in Moscow and its numerous contact points all over Europe. These radio telegrams were intercepted and decrypted by British Intelligence in the years 1934–37. The result of this effort was a collection of more than 8.000 documents, which for decades were kept secret in London. They were declassified in the years following the collapse of Communism and the Soviet Union and are now available in electronic copies in the Royal Library in Copenhagen. This comprehensive material provides a new and sounder insight into the Comintern’s international networks and communication methods in the 1930s. More than ten percent of the intercepted telegrams consist of correspondence between Moscow and the special contact point in Copenhagen. The article analyses both the political and the more “technical” directives that reached Copenhagen and other European capitals and also uncovers the intensive traffic by communist couriers, agents, etc., between the Soviet Union and Denmark during this period. In a separate section that deals with the wider courier traffic in Europe it is documented that Danish couriers based in Moscow were very active in transporting large amounts of money to Paris, Stockholm, Prague and elsewhere. In just a little more than a year, Danish couriers Ellen Schou and Gottlieb Japsen transported suitcases from Moscow to various European capitals with an amount equivalent to DKK 24 million in 2014. The material also shows that four out of five identified money couriers in 1936 were women and that Swedish citizens in particular played a prominent role among the couriers. Finally, the article outlines the frameworks for future analysis of the entire collection of decrypted radio telegrams.